The Development of Emotional Programmes in Education Settings during the Last Decade - Beatriz Muñoz-Oliver; Pedro Gil-Madrona; José Luis Gómez-Ramos (MDPI AG, 2022)
Within the psychological domain of emotional intelligence, experimentation on emotional education programmes in school contexts constitutes one of the most compelling research lines in recent years. On this basis, this study presents a review of forty-one programmes implemented in educational settings. The results obtained from the primary and secondary scrutinised sources show the need to integrate families into programme interventions and the importance of teacher training in socio-emotional competencies. Likewise, the importance of interconnecting natural educational settings with research activity is considered a fundamental aspect in designing, implementing, and evaluating such programmes. Thus, the present study aims to represent these programmes' characteristics, evaluation, and results for the ulterior development of specific and contextualised proposals.